Dinamika Politik Lokal ‘Daerah Istimewa Yogyakarta’: Suatu Analisis dari Perspektif Kulturalis - Zakia, Malika; Fitri, Catur; Addiansyah, M. Nur Rafiq; Addiansyah, M. Nur Rofiq (Fakultas Adab dan Humaniora UIN Raden Fatah, 2024)
This article will discuss the dynamics of local politics in the Special Region of Yogyakarta which is analyzed through a culturalist perspective. In this research, culturalist theory is used to analyze whether the granting of special autonomy to Yogyakarta will be able to produce a culture, politics and economy that is different from other regions (which are not given special regional autonomy). The research method used to analyze written problem formulations is a qualitative method with data analysis in the form of descriptive analysis. Data collection was carried out through literature studies, obtained from similar research in the form of journals, articles and online news to support research. The results of this research reveal that the dynamics of the 'Yogyakarta Special Region' through a culturalist perspective provide an explanation that culture gives rise to an influence on politics as a whole. In D. I. Yogyakarta, there is a long historical journey in fighting for their culture to be maintained to this day. Until the birth of Law Number 13 of 2012 concerning the Yogyakarta Special Region Law which grants special autonomy to the Yogyakarta Special Region to manage its own region. The recommendation of this research is the need for further research by future researchers regarding the special legislation of the Special Region of Yogyakarta from different perspectives or theories.